Pengelolaan Sampah di SMP Negeri 2 Cikarang Pusat, Kabupaten Bekasi - Windi, Windi; Aguswin, Ahmad; Akromusyuhada, Akhmad; Sukandi, Pipin; Syah, Dika Argiyan (Indonesian Journal of Society Engagement, 2024)
Community service activities carried out at SMP Negeri 2 Cikarang Pusat, Bekasi Regency, are a form of concern for the environment around the school. Although the waste produced has not been processed, it has been collected and disposed of. The process of collecting waste often causes problems, especially related to pollution and unpleasant odors. This problem may be caused by the lack of awareness of students about the importance of waste management in the school environment. To overcome this problem, community service activities are carried out through training for students regarding environmental concern based on waste management. This training is carried out inside and outside the classroom, including waste sorting and waste processing and its economic potential. Through the practice of waste processing that has economic value, it is hoped that students can have broader insights and increase their entrepreneurial spirit. The process of this activity also aims to create a cleaner and more comfortable school environment, by preventing the accumulation of waste in the school environment.